Single-Molecule Measurements of Transient Biomolecular Complexes through Microfluidic Dilution - Horrocks, Mathew H. (American Chemical Society, 2013)
[Image: see text] Single-molecule confocal microscopy experiments require concentrations which are low enough to guarantee that, on average, less than one single molecule resides in the probe volume at any given time. Such concentrations are, however, significantly lower than the dissociation constants of many biological complexes which can therefore dissociate under single-molecule conditions. To address the challenge of observing weakly bound complexes in single-molecule experiments in solution, we have designed a microfluidic device that rapidly dilutes samples by up to one hundred thousand times, allowing the observation of unstable complexes before they dissociate. The device can interface with standard biochemistry laboratory experiments and generates a spatially uniform dilution that is stable over time allowing the quantification of the relative concentrations of different molecular species.